Wearable microtechnology can accurately identify collision events during professional rugby league match-play - Hulin, B. T.; Gabbett, T. J.; Johnston, R. D.; Jenkins, D. G. (Journal of Science and Medicine in Sport, 2017)
Objectives: Collision frequency during rugby league matches is associated with team success, greater and longer lasting fatigue and increased injury risk. This study researched the sensitivity and specificity of microtechnology to count collision events during rugby league matches. Design: Diagnostic accuracy study. Methods: While wearing a microtechnology device (Catapult, S5), eight professional rugby league players were subjected to a total of 380 collision events during matches. Video footage of each match was synchronised with microtechnology data. The occurrence of each collision event was coded in comparison with whether that event was or was not detected by microtechnology. Results: Microtechnology detected 371 true-positive collision events (sensitivity = 97.6 ± 1.5%). When low-intensity (<1 PlayerLoad AU), short duration (<1 s) events were excluded from the analysis, specificity was 91.7 ± 2.5%, accuracy was 92.7 ± 1.3%, positive likelihood ratio was 11.4 ×/÷ 1.4 and the typical error of estimate was 7.8% ×/÷ 1.9 (d = 0.29 ×/÷ 1.9, small). Microtechnology collisions were strongly and positively correlated with video coded collision events (r = 0.96). The ability of microtechnology to detect collision events improved as the intensity and duration of the collision increased. Conclusions: Microtechnology can identify 97.6% of collision events during rugby league match-play. The typical error associated with measuring contact events can be reduced to 7.8%, with accuracy (92.7%) and specificity (91.7%) improving, when low-intensity (<1 PlayerLoad AU) and short duration (<1 s) collision reports are excluded. This provides practitioners with a measurement of contact workload during professional rugby league matches.